(untitled) (Academicia Globe: Inderscience Research, 2021)
In order to increase the investment activity of enterprises in the national economy, attract and effectively use foreign investment, the country implements public investment programs. These programs serve to technically re-equip manufacturing enterprises, implement production and economic modernization programs, and ensure sustainable economic growth.